Innovative Applications of Wearable Electronic Textiles in Health Monitoring: From Smart Socks to Scoliosis Corrective Garments: A Practical Exploration - Yao, Wenzhu (International Journal of Social Sciences and Public Administration, 2025)
Wearable electronic textiles, the result of a deep integration of flexible electronics and traditional textile processes, are profoundly transforming the field of health monitoring. This article focuses on innovative practices, systematically examining the technical pathways and application value of wearable electronic textiles, from foot health to spinal management. Taking smart socks as an example, their core lies in the direct weaving of fabric pressure, temperature, and humidity sensors into the sock body. This integration enables continuous monitoring of plantar pressure distribution and local microenvironmental changes, providing dynamic assessment and early warning of diabetic foot ulcer risk, significantly enhancing patients’ self-management capabilities. In the field of scoliosis management, smart orthotic garments are breaking through the limitations of traditional braces. By embedding a network of fabric strain sensors within key garment structures, they capture three-dimensional torso posture changes and pressure distribution in real time. Combined with analysis by a built-in microprocessor, the system provides instant biofeedback and dynamically optimizes correction force, establishing a closed-loop management system of "real-time monitoring - immediate feedback - precise intervention," effectively improving treatment compliance and clinical outcomes. The article further explores the potential and key challenges of this technology in scenarios such as long-term chronic disease monitoring, postoperative functional recovery tracking, and sports biomechanical analysis. Core challenges include ensuring the long-term stability of sensor signals in complex environments, ensuring the comfort and durability required for extended daily wear, safeguarding user privacy and security associated with collecting physiological data, and overcoming the bottlenecks of large-scale, low-cost manufacturing processes necessary for market adoption. Existing practices demonstrate that wearable electronic textiles, with their "burdenless" integration and continuous monitoring and intervention capabilities, are quietly reshaping health management models and driving the shift toward personalized, preventative healthcare. Future breakthroughs will rely heavily on the deep integration and collaborative innovation of multiple disciplines, including materials science, microelectronics, intelligent algorithms, and clinical medicine.